Evolution Game Model of Travel Mode Choice in Metropolitan - Chaoqun Wu; Yulong Pei; Jingpeng Gao (Discrete Dynamics in Nature and Society)
The paper describes an evolution game model of travel mode choice to determine whether transportation policies would have the desired effect. The model is first expressed as a two-stage sequential game in the extensive form based on the similarity between evolution game theory and the travel mode choice process. Second, backward induction is used to solve for Nash equilibrium of the game based on the Folk Theorem. Third, the sensitivity analysis suggests that a payoff reduction of travel by any mode will result in a rising proportion of inhabitants travelling by that mode and falling proportions of inhabitants travelling by other modes. Finally, the model is applied to Beijing inhabitants’ travel mode choices during morning peak hours and draws the conclusion that the proportion of inhabitants travelling by rail would increase when traffic congestion is more severe. This confirms that fast construction of the urban rail transit would be an effective means of alleviating traffic congestion. The model may be a useful tool for policy makers for analyzing the complex influence of travel mode choice processes on transport policies and transport construction projects.